Utilization of Service Set Identifiers (SSID) with ESP-01 in Wireless Networks for Lighting Automation - Julham; Putra, Purwa Hasan; Ramli, Muslim (Yayasan Asmin Intelektual Berkah, 2024)
Wireless networks better known as WiFi (Wireless Fidelity) are often used as a medium for exchanging data, for example: the internet. Each WiFi is equipped with an identity so that users can connect. This identity is known as SSID (Service Set Identifier). In this research, the focus is on assembling the SSID sensor which aims to detect the SSID as well as connect the SSID. So if the connection is successful, the light will be on. This happens because the lamp is connected to an electricity source, and vice versa, the lamp goes out because the lamp is not connected to an electricity source. The description of the system created consists of an input part and a process part, namely the ESP-01 which is capable of providing WiFi, and an output part, namely the relay. From controlling the light conditions, it was found that the average time required to change conditions from on to off was 3.052 seconds and the average time required to change conditions from off to on was 3.036 seconds.